Science Identity and Its “Identity Crisis”: On Science Identity and Strategies to Foster Self-Efficacy and Sense of Belonging in STEM - Sandrone, Stefano (Frontiers in Education, 2022)
The word identity etymologically derives from the Latin expression identitas, from idem, which means same. But the identities each of us has in the same moment and across life stages can be multiple and continuously changing, and are influenced by internal (i.e., personal) and external (i.e., environmental) factors. In this manuscript, I reviewed the existing literature on the theoretical and practical aspects of science identity across school levels. I explored how it can be measured and shed light on the links between science identity, professional identity, mentoring and sense of belonging. Then, I analysed strategies to foster self-efficacy and sense of belonging in STEM, with the aim of creating a scientific community that is genuinely inclusive and diverse. A set of recommendations to build a community with shared goals and enhanced diversity, with beneficial effects at several societal levels, has been included.